Biodegradable PBAT/PLA/CaCO3 Blowing Films with Enhanced Mechanical and Barrier Properties: Investigation of Size and Content of CaCO3 Particles. Issue 9 (2nd June 2022) - Ma, Fahang; Wang, Bo; Leng, Xuefei; Wang, Ying; Sun, Zhijing; Wang, Pei; Sang, Lin; Wei, Zhiyong
Abstract: Biodegradable poly(butylene adipate‐co‐terephthalate)/poly(lactic acid)/calcium carbonate (PBAT/PLA/CaCO3 ) blend films with variable compositions are prepared using one‐step melt‐blending and a following film‐blowing. The effects of CaCO3 content and particle size on the physicochemical properties of the films are investigated. The rheology results demonstrate that the storage modulus and complex viscosity are increased with the increasing CaCO3 content. The tensile performance and tear resistance including both the machine direction (MD) and transverse direction (TD) are also improved by adding CaCO3 . Especially, P7/P3/C3000 30 achieves the highest tensile and tearing strength in MD of 31 ± 2.5 MPa and 99 ± 4.0 N mm −1, respectively. Compared with unfilled PBAT/PLA films, the water vapor transmission greatly declines from 621 to 287 g m −2 24 h and the oxygen transmission values are also reduced from 1400 to 1010 cm 3 m −2 d Pa after the incorporation of CaCO3 particles. A slight decrease in thermal stability is detected in PBAT/PLA/CaCO3, but overall, the decomposition temperature is much higher than the processing and service temperature. Therefore, the biodegradable PBAT/PLA films with low‐cost CaCO3 fillers demonstrate excellent mechanical and oxygen and moisture barrier performance, which show great potentials in food‐packaging and mulch film in the agriculture field. Abstract : Biodegradable poly(butylene adipate‐co‐terephthalate)/poly(lactic acid)/calcium carbonate (PBAT/PLA/CaCO3 ) blend films are successfully prepared. The addition of CaCO3 not only improves the tensile strength and tear resistance, but also enhances the water vapor and oxygen barrier properties. The fabricated blend films show great potentials in food‐packaging and mulch film in the agriculture field.